Ефективний UX/UI-дизайн для криптопроєктів - Ракітіна, В. О. (ХНУРЕ, 2025)
Effective UX/UI design plays a crucial role in the success of cryptocurrency projects. A well-designed website fosters user trust, attracts investors, and ensures ease of interaction. Elements such as a concise whitepaper, an updated roadmap, and a comprehensive FAQ section are essential for transparency and user engagement. The homepage should feature recognizable branding, fast load times, and a smooth registration process. Regularly updated content, social media, and educational materials help maintain audience interest. Localization for different languages can significantly expand the project's reach globally.
Keywords: UX/UI-дизайн; криптопроєкт